Hubungan Interpersonal Pengguna Dating Apps Bumble (Studi Kualitatif Hubungan Interpersonal Generasi Z Melalui Dating Apps Bumble) - Triandini, Raisya Aqilah; Sumardjijati, Sumardjijati; Tutiasri, Ririn Puspita (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to understand how interpersonal relationships are formed and developed among Bumble users, especially Generation Z, through the Bumble dating app. Using a descriptive qualitative approach, this study involved 8 Bumble user informants aged 19-27 years who live around cities, especially in East Java Province who were interviewed. Bumble facilitates introductions, the success of relationships depends on self-disclosure, trust, consistent communication, and emotional readiness. Most interactions fail when reaching the affective or stable exchange stage that has been explained in Social Penetration Theory is the main concept used to explain the developmental phases of interpersonal relationships, starting from orientation, affective exploration, affective exchange, and ending at the stable exchange stage. The theoretical implications of this study strengthen the relevance. In conclusion, Bumble functions as an intermediary medium, while the dynamics of user communication determine the sustainability of interpersonal relationships.